2022
DOI: 10.1075/elt.00039.hog
|View full text |Cite
|
Sign up to set email alerts
|

Social and sensory influences on linguistic alignment

Abstract: Previous research has demonstrated that speakers adapt individual characteristics of speech production to the social context, for example via phonetic convergence. Studies have measured the impact of social dynamics on convergence in typical speakers, but the impact of individual differences is less well-explored. The present study measures phonetic convergence before and after a cooperative interaction with an undergraduate student by comparing teens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 65 publications
0
4
1
Order By: Relevance
“…In addition to the findings of vowel formants, autistic children entrained their mean f0 comparably to their TD peers. This result was inconsistent with some previous studies, where neither autistic nor TD children showed prosody entrainment (Hogstrom et al, 2018;Wynn et al, 2018). As most studies computed the differences between conversation partners to indicate phonetic entrainment, it is very likely that their findings about entrainment or lack of entrainment was actually driven by the adjustment of their interlocutors.…”
Section: Discussioncontrasting
confidence: 89%
See 3 more Smart Citations
“…In addition to the findings of vowel formants, autistic children entrained their mean f0 comparably to their TD peers. This result was inconsistent with some previous studies, where neither autistic nor TD children showed prosody entrainment (Hogstrom et al, 2018;Wynn et al, 2018). As most studies computed the differences between conversation partners to indicate phonetic entrainment, it is very likely that their findings about entrainment or lack of entrainment was actually driven by the adjustment of their interlocutors.…”
Section: Discussioncontrasting
confidence: 89%
“…In addition, children as young as 9 years old were found to converge in mean f0 in "spot-the-difference" games in Lehnert-LeHouillier et al (2020). Hogstrom et al (2018) also reported convergence of phoneme duration from children aged from 12 to 18 in a cooperative map searching task.…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…Particularly, we carried out a study on phonetic convergence between children with Autism Spectrum Disorder (ASD) and typical developing (TD) children. Atypical social behaviour is one core feature of ASD population (American Psychiatric Association, 2013), and it has been reported that they lack phonetic convergence in conversations with human beings (Hogstrom et al, 2018;Wynn et al, 2020). Therefore, we raised the following research questions: 1) do ASD and TD children show phonetic convergence in a conversation with a social robot?…”
Section: Introductionmentioning
confidence: 99%